Odpowiedzi

2010-03-04T17:14:24+01:00
C)5x+0,6y+4
d)8 1/3x-5/9y-3
2010-03-04T17:25:45+01:00
C ) = -2x - 3y + 4 = - 2 *( - 0,5 ) - 3 * 0,1 + 4 = 1 - 0,03 + 4 = 0,97 + 4 = 4,97

d) = - 3x - 5y - 3 = - 3 * ( 1 1/3 ) - 5 * 1/9 - 3 = 1 - 2,5/4,5 - 3 = 1 - 5/9 - 3 = 1/1 - 5/9 - 3/1 = - 5/3
2010-03-04T17:53:11+01:00
C) ( -6 * [-0,5]) + ( 2 * 0,1 ) + 7 + ( 4*[-0,5])+ (-5*0,1) - 3 =
3+0,2+7-2-0,5-3= 4,7

d) (2*[-1,1/9])+ (-6*1/9 ) + 8 + (-5*[-1,1/9]) +1/9-11=
-2²/₉ - ²/₃ +8+5⁵/₉ + ¹/₉ - 11=
-2⁸/₉ + 13⁵/₉ + ¹/₉-11=
10²/₃+¹/₉ - 11 =
10⁷/₉ - 11 = - ²/₉